Community Assistance to Optimize Child Identity Cards (KIA) As A Means of Payment Through Population Administration Services in Sukolilo District - Fransiska Ajustina; Oktafia, Renny (IJCS: International Journal of Community Service, 2023)
From year to year, the growth of the population continues to increase. Each citizen has the duty and right to report population events and obtain official population documents to be recognized as citizens. Every citizen is required to have population documents, one of which is the Child Identity Card (KIA). The increasing population growth can lead to the emergence of population administration issues. Some communities still do not have population administration documents, such as Child Identity Cards. This is due to the lack of awareness among the public about the importance of population administration, a lack of understanding of the benefits of the Child Identity Card, and limitations in technological knowledge. Therefore, the government issues policies and innovations to address these issues. The aim of this activity is to improve the distribution and optimization of the Child Identity Card (KIA) as a payment tool. In implementing this service activity, the Asset Based Community Development (ABCD) method is used. The ABCD method is a concept of empowering communities by utilizing the assets or potentials that the community possesses. Through various stages, this can increase the level of self-awareness in the community and enhance the distribution of the Child Identity Card as a payment tool in the city of Surabaya, impacting various fields, especially in population and the economy.